IT @ Organized Retail Management - Arora, Suneel; Vyas, Mukesh (Indian Journal of Marketing, 2006)
As retailers realign themselves to meet the expectations and demands of a consumer who is more informed, has an increasing number of choices and less time than ever, technology’s traditional role as an operational problem solver is undergoing a seismic shift. In fact, technology innovations in all areas of the enterprise are offering retailers unprecedented opportunities to shape their offerings, and indeed their entire strategic direction, to meet customers’ needs and exceed their expectations. This paper examines the prevalent IT business methods and models in the management of Organized Retail.